Preserving the legacy the semiconductor and electronics industry - Weisman, David (Environmental awareness, 1997)
This programme presents an overview of the semiconductor and electronics industry. It focuses on integrated circuit design, fabrication, and related ozone issues involving solvent handling, replacement or substitution.